The Role Of Caregivers In The Formation Of The Discipline Character Of The Institution Of Domestic Government West Sumatra Campus - Toni K. Nainggolan; Dasep Suryanto (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2025)
This study explores the role of mentors in character-building strategies for cadets at the Institute of Public Administration (IPDN) West Sumatra Campus. Using a qualitative case study design, data were collected through interviews, observations, and documentation, validated via source triangulation. Results show that mentors are central figures in enforcing discipline and shaping values through consistent guidance and exemplary behavior. Despite institutional frameworks, challenges such as insufficient mentor capacity and generational shifts impact the effectiveness of character formation. The study highlights the need to strengthen mentor competencies and improve character education programs to ensure cadets develop strong leadership values and integrity.